Directions in plasma wakefield acceleration. (24th June 2019) - Hidding, B.; Foster, B.; Hogan, M. J.; Muggli, P.; Rosenzweig, J. B.
Abstract : This introductory article is a synopsis of the status and prospects of particle-beam-driven plasma wakefield acceleration (PWFA). Conceptual and experimental breakthroughs obtained over the last years have initiated a rapid growth of the research field, and increased maturity of underlying technology allows an increasing number of research groups to engage in experimental R&D. We briefly describe the fundamental mechanisms of PWFA, from which its chief attractions arise. Most importantly, this is the capability of extremely rapid acceleration of electrons and positrons at gradients many orders of magnitude larger than in conventional accelerators. This allows the size of accelerator units to be shrunk from the kilometre to metre scale, and possibly the quality of accelerated electron beam output to be improved by orders of magnitude. In turn, such compact and high-quality accelerators are potentially transformative for applications across natural, material and life sciences. This overview provides contextual background for the manuscripts of this issue, resulting from a Theo Murphy meeting held in the summer of 2018. This article is part of the Theo Murphy meeting issue 'Directions in particle beam-driven plasma wakefield acceleration'.